Orienteering Certification Course provided exposure to Water Sports Enthusiasts in the country - Siti Nurfarmy, Ibrahim (2019)
Universiti Malaysia Pahang (UMP)’s Sports and Culture Centre joined forces with Magnetic Edge Orienteering Sports Club (MEOSC) and Academy of Orienteering Malaysia (AOM) to organise, for the first time, a Level One Orienteering Certification Course for water sports enthusiasts in the country.